Aspek Masalah Kepailitan Dalam Tataran Teori Dan Problematikanya Yang Berlaku Di Indonesia - Irawan Fakhrudin Mahalizikri (LPPM ISNJ Bengkalis, 2015)
Global Economic growth influence on the development of the law, especially commercial law which is the driving wheels of the economy. globalization of law will lead to developing countries regulations on investment, trade, services and other economic sector approach developed countries (convergence). In order to adapt to the global economy, Indonesia to revise the entire legal economy. changes to the law of the Indonesian economy performed well due to pressure from world bodies like the WTO, IMF, and the World Bank. Revised legal field include bankruptcy law, which is a legacy of the Dutch colonial administration Unsurprisingly patterned continental European legal systems. In Indonesia, this time in the economic law got a strong influence of the Anglo-Saxon legal system. The problem is when a company as a debtor or a party that has a debt due to the agreement or laws that repayment can be billed in court, was unable to repay the debt from the creditor or debt receivable parties for agreements or laws that can be charged in court repayment. Therefore, to ensure fairness to both parties, the government passed a law on bankruptcy. Bankruptcy arrangement has existed since the Dutch colonial in the era, namely S.1905-217 conjunction S.1906-348. To ensure legal certainty more certain than on April 22 1998, was issued Regulation No. 1 of 1998 which was adopted by Act 1 of 1998. To ensure legal certainty more certain than on April 22 1998, was issued Regulation No. 1 of 1998 which was adopted by Act 1 of 1998. Act 1 of 1998 is repaired and replaced by Act No. 37 of 2004 on Bankruptcy and Suspension of Payment of Debts. Bankruptcy is common to all the wealth confiscation Bankrupt Debtor that the maintenance and finalized performed by curators under the supervision of the Supervisory Judge as provided in this Act. This legislation increasingly answering share bad credit problems that exist in Indonesia at that time.